PENINGKATAN MOTIVASI BELAJAR MATEMATIKA MELALUI MEDIA INTERAKTIF BERBASIS CANVA PADA SISWA KELAS III SD - Annisa Humaila; Zhafira Sayyidatunnisa (STKIP Subang, 2026)
Low learning motivation in mathematics among elementary school students is a common problem encountered in daily classroom practice. Students in lower grades, particularly grade III, often perceive mathematics as a difficult, boring, and unpleasant subject, which negatively affects their engagement and enthusiasm for learning. This situation is exacerbated by the use of conventional teaching methods that insufficiently address students' visual needs and interests. This study aims to describe the improvement of mathematics learning motivation among grade III elementary school students through the application of Canva-based interactive media. This study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart spiral model, consisting of four stages in each cycle: planning, action, observation, and reflection. The research was conducted in two cycles, each consisting of three meetings. The research subjects were 25 third-grade students at a public elementary school. Data collection instruments included teacher and student activity observation sheets, a learning motivation questionnaire using a Likert scale (1–4), field notes, and documentation. Data were analyzed using quantitative and qualitative descriptive techniques. The results revealed a significant improvement in learning motivation. Before the intervention (pre-cycle), only 28% of students were in the high motivation category. After implementing Canva-based interactive media in cycle I, this percentage increased to 56%. In cycle II, it rose further to 84%. This improvement was supported by the visually appealing Canva media, interactive content presentation, and the addition of gamification elements in cycle II. These findings indicate that Canva-based interactive media is effective as an innovative mathematics learning tool to improve the learning motivation of grade III elementary school students.